The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-20534-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ochratoxin A contamination in grapes, processed grape products and animal-derived products using ultra-performance liquid chromatography-tandem mass spectroscopy system

Abstract: We developed a sensitive and rapid analytical method to determine the level of Ochratoxin A contamination in grapes, processed grape products and in foods of animal origin (a total of 11 different food matrices). A pretreatment that followed a “quick, easy, cheap, effective, rugged, and safe” protocol was optimized to extract Ochratoxin A from the matrices, and the extracted Ochratoxin A was then detected with the use of a highly sensitive ultra-performance liquid chromatography-tandem mass spectrometry system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Real Sample Analysis. Ultraperformance liquid chromatography (UPLC) was used to compare both standard OTA solutions and spiked-beer samples, obtained from a local store, using conditions as reported by Wei et al 25 Beer samples were degassed with argon gas before being directly applied to either the aptasensor electrode or UPLC analysis. Testing was performed by spiking OTA into beer at concentrations of 1, 10, and 100 ng mL −1 .…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Real Sample Analysis. Ultraperformance liquid chromatography (UPLC) was used to compare both standard OTA solutions and spiked-beer samples, obtained from a local store, using conditions as reported by Wei et al 25 Beer samples were degassed with argon gas before being directly applied to either the aptasensor electrode or UPLC analysis. Testing was performed by spiking OTA into beer at concentrations of 1, 10, and 100 ng mL −1 .…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In Poland, 26.7% (16/66) of grape beverages tested positive for OTA at the highest value of 0.7 µg/kg [ 26 ]. Wei et al analyzed 41 grape juices and found that all of the samples were exposed to OTA, the incidence of positives was 100% and the OTA concentration of six grape juice samples was between 0.1 and 0.2 μg/kg [ 27 ]. In Iran, it was found that the OTA level of 39 out of 70 samples (55.7%) was higher than 2 µg/L, and the upper bound mean was 2.6 μg/L [ 28 ].…”
Section: Occurrence Contamination and Toxicity Of Mycotoxinsmentioning
confidence: 99%
“…Ochratoxin A (OTA) is a secondary fungal metabolite produced by filamentous fungal strains, viz., Aspergillus and Penicillium species. OTA possess severe health risks if ingested including nephrotoxicity and hepatotoxicity, and it is a potential carcinogen (Akdeniz et al, 2013;Wei et al, 2018). The European Union set OTA maximum accepted levels in grape products as juice, nectar, and wine not to exceed 2 µg/kg (Commission, 2005).…”
Section: Aspergillus and Penicillium Toxinsmentioning
confidence: 99%
“…The European Union set OTA maximum accepted levels in grape products as juice, nectar, and wine not to exceed 2 µg/kg (Commission, 2005). Different analytical procedures have been developed for the detection of these toxins in grapes, wine, juice, and other food products (Wei et al, 2018). Patulin is a toxic metabolite produced by Aspergillus and Penicillium with possible human hazards being carcinogenic and to be monitored in fruit juices including that of grape (Cho et al, 2010;Rahimi & Rezapoor Jeiran, 2015).…”
Section: Aspergillus and Penicillium Toxinsmentioning
confidence: 99%